Pyrrhotite-troilite intergrowth from Luikonlahti copper deposit, eastern Finland - A. Vorma (Bulletin of the Geological Society of Finland, 1970)
A homoaxial intergrowth of troilite with iron-deficient pyrrhotite, Fe0.921S, is described. X-ray single crystal study of the pyrrhotite component points to a superstructure with c = 11 C and apparently to an orthorhombic symmetry. The intergrowth occurs on fissure walls in serpentinite rock as euhedral long-prismatic crystals; it apparently formed at a very low temperature. Possibly a simultaneous crystallization of troilite and iron-deficient pyrrhotite took place.